Hidden Davidic and Solomonic Legends in The Hundred and One Nights: Backgrounds in Muslim Tradition Echoing the Bible and Midrash - Lerner, Amir (Medieval encounters, 2021)
This paper focuses on what can be identified as ancient Davidic and Solomonic biblical and midrashic narratives, echoed in some of the core stories of The Hundred and One Nights, a story collection in Arabic that took shape among lower strata of medieval society in western part of the Muslim world. We do not identify any specific written Jewish sources as having had a direct influence on the collection. Rather, we would like to reveal some of the contents of an ancient well of themes that were available, mostly through Muslim tradition, to those involved in the formation of the work in question. We would also like to point out some of the transformations that such contents have undergone in their shifting between religious, historical and literary levels. The existence of Jewish backgrounds in medieval Arabic literature in general is well-known. However, a more complete picture of this existence requires a comprehensive study of popular literature. As the theme of The Hundred and One Nights and its Jewish background has been overlooked by research until very recently, our study strives to address this lacuna.